Global software development governance: Challenges and solutions. Issue 10 (20th April 2020) - Manjavacas, Antonio; Vizcaíno, Aurora; Ruiz, Francisco; Piattini, Mario
Abstract: Global software development (GSD) has become a rising software development model in the last few years. Although much research has been performed in terms of GSD management, GSD governance research is scarce at the present time and presents multiple challenges that need to be addressed. In this paper, a systematic mapping study has been conducted, the aim of which was to discover the main issues dealt with in GSD governance literature, as well as to point out the particular research gaps that are still present in this domain. This allowed us to find out new challenges to be addressed, along with possible solutions to these. The results reveal a lack of research in key aspects such as tools, culture, people, and information, all of which provides a great opportunity for future approaches while also highlighting new opportunities in GSD governance research.